ANALYZING THE IMPACT OF ORGANIZATIONAL CHANGE AND CULTURE ON EMPLOYEE SATISFACTION AND PERFORMANCE AT THE UPT RADIO FREQUENCY SPECTRUM MONITORS - Mahyudin; Dg. Parani, Syamsul Bahri; Adda, Harnida Wahyuni (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
The objective of this study aims to evaluate the direct & indirect effects of organizational structure changes & organizational culture on employee performance, mediated by employee satisfaction, within the UPT Radio Frequency Spectrum Monitoring Office, Directorate General of Post & Information Resources & Equipment, Ministry of Communication & Information. A quantitative approach was used, with data collected from employees at six Radio Frequency Spectrum Monitoring UPT Offices across the Sulawesi region. The study employed Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis on a total sample of 111 respondents. Data were gathered through a questionnaire distributed via Google Forms. The study finds that :  (1) Organizational changes have a positive & significant effect on employee performance at the UPT Radio Frequency Spectrum Monitoring Office; (2) Organizational culture significantly & positively influences employee performance; (3) Organizational changes significantly & positively impact employee satisfaction; (4) Organizational culture has a positive & significant effect on employee satisfaction; (5) Employee satisfaction positively & significantly affects employee performance; (6) Organizational changes positively influence employee performance through the mediating role of employee satisfaction; & (7) Organizational culture positively affects employee performance, mediated by employee satisfaction.